2023
DOI: 10.3390/rs15205001
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Water Quality Parameters in Dianshan Lake Based on Sentinel-2 MSI Imagery and Machine Learning: Algorithm Evaluation and Spatiotemporal Change Research

Lei Dong,
Cailan Gong,
Hongyan Huai
et al.

Abstract: According to current research, machine learning algorithms have been proven to be effective in detecting both optical and non-optical parameters of water quality. The use of satellite remote sensing is a valuable method for monitoring long-term changes in the quality of lake water. In this study, Sentinel-2 MSI images and in situ data from the Dianshan Lake area from 2017 to 2023 were used. Four machine learning methods were tested, and optimal detection models were determined for each water quality parameter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It enhances the performance of the model by constructing multiple decision trees and averaging or voting their prediction results. Random Forest is typically characterised by high robustness and interpretability, making it an appropriate choice for problems that require high interpretability and stability [22,23,[38][39][40].…”
Section: Random Forestmentioning
confidence: 99%
See 2 more Smart Citations
“…It enhances the performance of the model by constructing multiple decision trees and averaging or voting their prediction results. Random Forest is typically characterised by high robustness and interpretability, making it an appropriate choice for problems that require high interpretability and stability [22,23,[38][39][40].…”
Section: Random Forestmentioning
confidence: 99%
“…At present, the most commonly employed machine learning algorithms for the retrieval of water quality parameters include regularised linear regression (LRR), random forest regression (RFR), kernel ridge regression (KRR), Gaussian process regression (GPR), and support vector machine regression (SVR) [6]. Previous studies have demonstrated that XGBoost and CatBoost are effective tools for water quality monitoring [23]. The objective of this study is to further explore the performance of ensemble learning algorithms in monitoring TN and TP in order to improve the accuracy and reliability of TN and TP monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Previous studies also showed a consistent tendency that the DO was lower in summer than in winter. For example, a shallow lake in southern America called University Lake was investigated by Xu et al [50], as well as Xianvu Lake [51], Dianshan Lake [52], and Tianmu Lake [53], which are all located in the southeast of China and have similar climates to the study area. The study of Dianshan Lake also showed that the COD Mn and TN were higher in summer and autumn, while the TP showed an opposite trend.…”
Section: Seasonal Differences Of Water Qualitymentioning
confidence: 99%
“…Based on the water quality data of Dongjiang Lake obtained from the water quality monitoring stations in the watershed, this study identified the dissolved oxygen index (DO), permanganate index (COD Mn ), chemical oxygen demand index (COD), ammonia nitrogen index (NH 3 -N) and total phosphorus index (TP) as the main water quality parameters in the study area [26]. The correlation relationship between each parameter and Landsat multispectral images was established, and the inversion models of five parameters were constructed.…”
Section: Inversion Of Water Quality Variablesmentioning
confidence: 99%